Does the Institutional Pressure in KSA Affects the Application of Green Supply Chain Business Model - Sami Mohamed AlHaderi (International Journal of Supply Chain Management, 2019)
In the present research, we attempt to provide evidence that having the effect of leadership and institutional pressures role as a moderator, the integration of TQM and supplier relationship management facilitate companies in achieving environmental performance. The literature [1] has well discussed how institutional pressures play their role in influencing the green supply chain practices adoption. The area which requires understanding is that how supplier relationship management, total quality management and leadership integration process are affected through institutional pressures on the firm’s environmental performance. Additionally, the institutional pressure is one of the key issues which are effecting the green supply chain mamagmnegt impnnetaion, therefore the study has examined the moderating role of institurioal pressure. Many scholars have made the studies on different sectors like manufacturing of electronic goods, gas and oil, automotive and components, whereas according to our knowledge we haven’t find any studies regarding petrochemical sector, which is the one of the main carbon emission source after deforestation, steel and refining of oil, transportation and cement. Secondly for undertaking a research project we got support from one of the petrochemical industry on Saudi Arabia , with respect to petrochemical and its handwork for the practices of green supply chain mamagmnegt. The findings of the study have provided support to the hypotehsied results.